Ejercicios de Frenkel en pacientes geriátricos con hemiparesia post ACV. - Carvajal Barzallo, Deyaneira Isabel (2024)
The purpose of this research project was to investigate bibliographic data describing the benefit of Frenkel's exercises in post-stroke hemiparesis. The rehabilitation of the hemiparetic patient became a problem of great relevance in the world since stroke indicates deterioration in the loss of the basic characteristics of voluntary movement. There are also activity limitations where it shows a decrease in the normal ability to independently perform activities of daily living. Recovery from impairment is achieved by restitution, and recovery from limitation is achieved by the combined effect of restitution and compensation. Through Frenkel exercises, both effects can be combined, helping balance and gait, improving coordination and proprioceptive control of affected people. The results were obtained through the bibliographic analysis of studies, such as: books, scientific articles, where the application of Frenkel's exercises over time and the results that can be verified are detailed. In the bibliographic search, 35 scientific articles evaluated by the PEDro scale were collected, leading to a documentary research based on the deductive method. The scientific databases collected were PubMed, Scielo, Sage Journal, Neurology Asia, NCBI. After the bibliographic search, the prevalence of the pathology in Latin America was evidenced, especially in countries such as Chile, Colombia and Ecuador due to their low epidemiology. Keywords: Stroke, Frenkel exercises, paresis, proprioception, sequelae and disability statistics, Rehabilitation and Patients.